Participation of Victorian Thoroughbreds in the racing industry: a whole‐of‐population benchmark. Issue 1 (30th September 2021) - Flash, ML; Crabb, HK; Hitchens, PL; Firestone, SM; Stevenson, MA; Gilkerson, JR
Abstract : The proportion of Thoroughbred (TB) horses that commence training and eventually race, is an important industry‐level indicator of how successful it is at producing horses suitable for racing. It is also of interest to the wider community and is central to the issue of whether there is overbreeding in the Australian TB industry. This study investigated the training and racing records for the 2005 and 2010 Victorian TB foal crops to determine the proportion of TBs that train and race, and the age of entering training and first race start. Subsets of the foal crop were also examined to determine if premier yearling sale cohorts would produce selection bias. The Australian Stud Book (ASB) registered 7662 TB horses born in Victoria in 2005 (n = 4116) and 2010 (n = 3546). Of these, 5614 (73%) entered training and 4868 (64%) started in at least one race. Fourteen percent (n = 1045) of the study cohort had their first race start as 2‐year‐olds and 35% (n = 2644) had their first start as 3‐year‐olds. A higher proportion of TB horses that attended premier yearling sales entered training (93%) and raced (84%). This study established a baseline for training and racing milestones, such as the proportion and age that horses commenced training, and age of first start using population‐level data. It also established that the use of subsets of the population can introduce selection bias.